Encouraging Entrepreneurial Orientation in The Traditional Craftsman Community in Tigawasa Village, Buleleng, Bali - Kusumawijaya Ida Ketut; Partiwi Dwi Astuti (International Journal Of Community Service, 2023)
The traditional craftsman community as a creative business is inherent in people's lives and is part of the microeconomic structure, becoming the daily economic activities of the community, especially bamboo woven craftsmen in the people of Tigawasa Village, Buleleng, Bali. The business activities of the traditional craftsman community are fundamental to encouraging the growth of the community's creative economy because these businesses are easy to set up, and do not require large resources. So often the business of this traditional craftsman community becomes a driving force for the creative economy with unique characteristics which is a sustainable competitive advantage for future. However, on the other hand, micro-enterprises of traditional craftsman community face various obstacles, including limited business capital, low entrepreneurial orientation of human resources, and inadequate mastery of technology and knowledge. This community service aims to encourage an entrepreneurial orientation in the traditional craftsman community in Tigawasa Village, Buleleng, Bali. The method of community service is a participatory action research approach that is oriented towards empowering and developing entrepreneurship and placing traditional craftsman communities as the main actors in developing the people's economy. These community service found three results, First, there is a change in the understanding and understanding of the traditional craftsmen community in Tigawasa Village regarding the importance of the entrepreneurial orientation role that craftsmen must have if they wish to be able to continue their business on an ongoing basis in the future. Second, the traditional craftsman community understands the practices and decision-making activities that lead to new entry, principally through risk-taking, innovation, proactive behaviors, and autonomy. Third, the traditional artisan community agrees that if they want to produce superior performance, they must have a strong entrepreneurial orientation. Because companies that have an entrepreneurial orientation show an increase in the number of products and services as well as growth in market share in order to survive and compete successfully.